Upaya Meningkatkan Aktivitas, Motivasi dan Hasil Belajar dalam Pembelajaran Membaca Pemahaman - Ayu Anindia; Ahmad Suriansyah (Jurnal Inovasi Pendidikan Dasar, 2021)
This study aims to improve teacher activities, student activities, student motivation, and learning outcomes using the MOTIVATION model, a combination of the DRTA, Scramble, and Talking Stick models. This research was conducted approach with four meetings. The subjects of this study were 28 students in fourth-grade students at Elementary School Pemurus Dalam 6 Banjarmasin. The data collection technique was an observation, questionnaire, and test. Data analysis using descriptive analysis and cross-tabulation analysis. The results showed that: 1) teacher activity increased to a score of 38 with a percentage of 95% of "Very Good" criteria; 2) student activity 100% of "Very Active" criteria; 3) student motivation 92.9% of "Very High" criteria; and 4) student learning outcomes increased 100% with "Very Good" criteria. Therefore, the MOTIVATION model can significantly increase teacher, student activity, motivation, and student learning outcomes.   Keywords: Learning Activities, Motivation, Learning Outcomes, Reading Comprehension Skills, MOTIVATION